Creative Historical System and Modern Project of the “Qirq Qiz” Fortress (Texas Journal of Multidisciplinary Studies, 2022)
Preservation of our unique historical monuments, such as the architectural monument of the “Qirqqiz” Fortress is a sacred duty of every citizen living in the territory of Uzbekistan. After all, without historical and modern spirituality, without the development of enlightenment, it is impossible to build a state governed by the rule of law and civil society in our country. The article describes this.